Pengaruh Senam Ling Tien Kung Terhadap Peningkatan Keseimbangan Tubuh Pada Lansia - Dwianto, Ignatius Heri (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Decreased body balance and increased risk of falling occur in the elderly population around 30-50% every year. Currently a partial exercise program is a solution given to strengthen certain muscles to support balance. With increasing age in the elderly, there will be a decrease in several components of the body system so that it will cause a decrease in balance. Prevention to reduce the risk of falling is to improve balance with ling tien kung exercise.Methods: This article uses a one group pretest posttest design with 30 participants as the subject of ling tien kung gymnastics which is divided into two groups, namely the pretest group (functional reach test and time up and go test before doing ling tien kung exercise) and the posttest group (functional reach test and time up and go after doing ling tien kung exercise for 1 month (8x), 2x in 1 week with 45 minutes). Data is collected and then analyzed statisticallyResults: The results of the normality test of the data on the balance variable with the Functional Reach Test (FRT) and the balance with the Time Up and Go Test (TUG) all showed p>0.05, so the data from this study were normally distributed. The results of the paired difference test with the paired t-test showed a balance of pre-post Functional Reach Test (FRT) with a significance value of 0.000 and a balance of pre-post Time Up and Go Test (TUG) with a significance value of 0.000. Because both showed a p value <0.05, there was a significant difference before and after the Ling Tien Kung exerciseConclusion: Â Â Ling Tien Kung exercise which is done within one month (8x), 2x a week for 45 minutes in the elderly can improve balance